The Genetic Structures of an Extensively Drug Resistant (XDR) Klebsiella pneumoniae and Its Plasmids - Li, Ling; Yu, Tao; Ma, Yanan; Yang, Zhongjun; Wang, Wenjia; Song, Xiaobo; Shen, Yu; Guo, Tingting; Kong, Jian; Wang, Mingyu; Xu, Hai (Frontiers in Cellular and Infection Microbiology, 2019)
Multi-, extensively-, and pan-drug resistant bacteria are a threat to our health today, because their wide resistance spectra make their infections difficult to cure. In this work, we isolated an extensively drug resistant (XDR) Klebsiella pneumoniae 2-1 strain from the stool sample of a patient diagnosed of colorectal cancer. K. pneumoniae 2-1 was found to be resistant to all the antibiotics tested except for cefepime, tigecycline, and ceftazidime-avibactam. By sequencing the complete genome of K. pneumoniae 2-1, we found it contains a chromosome of 5.23 Mb and two circular plasmids with the size of 246 kb and 90 kb. The larger plasmid, pKP21HI1 was found to be a new conjugation-defective plasmid belonging to incompatibility group HI1B and a new sequence type. Further comparative genomics analysis and antimicrobial resistance gene analysis showed that although a great deal of changes took place on the chromosome of K. pneumoniae 2-1 in comparison with the reference genome, the extensively drug resistance phenotype of K. pneumoniae 2-1 is primarily due to the two multidrug resistant plasmids it contains. This work explains the genetic and mechanistic basis of the extensive drug resistance of K. pneumoniae 2-1, and found that plasmids play key roles in the strong antibiotic resistance of bacteria.